The association between DNA methylation and exon expression in the Pacific oyster Crassostrea gigas. - Kai Song; Li Li; Guofan Zhang (PLoS ONE, 2017)
DNA methylation is one of the most important epigenetic modifications of eukaryotic genomes and is believed to play integral roles in diverse biological processes. Although DNA methylation has been well studied in mammals, data are limited in invertebrates, particularly Mollusca. The Pacific oyster Crassostrea gigas is an emerging genetic model for functional analysis of DNA methylation in Mollusca. Recent studies have shown that there is a positive association between methylation status and gene expression in C. gigas; however, whether this association exists at the exon level remains to be determined.In this study, we characterized the genome-wide methylation pattern across two different tissues of C. gigas and found that methylated genes are expressed in more tissues and development stages than unmethylated genes. Furthermore, we found that different types of exons had different methylation levels, with the lowest methylation levels in the first exons, followed by the last exons, and the internal exons. We found that the exons included in the gene transcript contained significantly higher DNA methylation levels than skipped exons. We observed that the DNA methylation levels increased slowly after the start sites and end sites of exons seperately, and then decreased quickly towards the middle sites of exons. We also found that methylated exons were significantly longer than unmethylated exons.This study constitutes the first genome-wide analysis to show an association between exon-level DNA methylation and mRNA expression in the oyster. Our findings suggest that exon-level DNA methylation may play a role in the construction of alternative splicing by positively influencing exon inclusion during transcription.